2022
DOI: 10.1002/cbin.11805
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine facilitates endoplasmic reticulum stress and apoptosis of hepatocytes by suppressing ERO1α expression via cooperation between DNMT1 and G9a

Abstract: Endoplasmic reticulum (ER) stress and apoptosis play a critical role in liver injury.Endoplasmic reticulum oxidoreductase 1α (ERO1α) is an oxidase that exists in the luminal side of the ER membrane, participating in protein folding and secretion and inhibiting apoptosis, but the underlying mechanism on liver injury induced by homocysteine (Hcy) remains obscure. In this study, hyperhomocysteinemia (HHcy) mice model was established in cbs +/− mice by feeding a high-methionine diet for 12 weeks; and cbs +/− mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…However, n6-methyladenosine (m6A) modification and editing can reverse this phenomenon and increase pyroptosis in pulmonary artery endothelial cells [ 151 ]. Under the interaction of DNMT1 and HMT G9a, homocysteine inhibits the expression of reticulo-oxidoreductase 1α (ERO1α), activates the occurrence of endoplasmic reticulum stress and hepatocyte apoptosis, causing liver injury [ 152 ]. In addition, DNA methylases are also involved in the progression of chronic kidney disease to renal cell carcinoma [ 153 ].…”
Section: Types Of Chromatin Modifiersmentioning
confidence: 99%
“…However, n6-methyladenosine (m6A) modification and editing can reverse this phenomenon and increase pyroptosis in pulmonary artery endothelial cells [ 151 ]. Under the interaction of DNMT1 and HMT G9a, homocysteine inhibits the expression of reticulo-oxidoreductase 1α (ERO1α), activates the occurrence of endoplasmic reticulum stress and hepatocyte apoptosis, causing liver injury [ 152 ]. In addition, DNA methylases are also involved in the progression of chronic kidney disease to renal cell carcinoma [ 153 ].…”
Section: Types Of Chromatin Modifiersmentioning
confidence: 99%
“…Using bioinformatic analysis, Liu et al and Shi et al found that the promoter methylation of ERO1α was markedly reduced in lung cancer, suggesting that hypomethylation of the promoter relieved transcription inhibition, resulting in the overexpression of ERO1α [64,67]. In a study focusing on liver cell apoptosis, DNA methyltransferase 1 (DNMT1) and G9a (also known as euchromatic histonelysine N-methyltransferase 2 (EHMT2)) were shown to be responsible for the reduction of ERO1α by mediating the hypermethylation and H3K9me2 modification of the ERO1α promoter, respectively [92].…”
Section: Regulation Of Ero1α In Tumorsmentioning
confidence: 99%